2022
DOI: 10.1590/0034-7167-2021-0586
|View full text |Cite
|
Sign up to set email alerts
|

Beyond technology: Can artificial intelligence support clinical decisions in the prediction of sepsis?

Abstract: Objective: To analyze the critical alarms predictors of clinical deterioration/sepsis for clinical decision making in patients admitted to a reference hospital complex. Methods: An observational retrospective cohort study. The Machine Learning (ML) tool, Robot Laura®, scores changes in vital parameters and lab tests, classifying them by severity. Inpatients and patients over 18 years of age were included. Results: A total of 122,703 alarms were extracted from the platform, classified as 2 to 9. The pre-selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(31 reference statements)
0
1
0
1
Order By: Relevance
“…Most studies reported MLA evaluations at stage II (retrospective), 32 , 33 , 36 , 38–40 , 45 , 48 , 49 , 55–57 2 at stage III (silent trial), 33 , 41 4 at stage IV (pilot trial), 50 , 58–60 3 at stage V (large trial/roll-out), 33 , 46 , 61 and 11 reported post-deployment evaluations. 35 , 37 , 42–44 , 47 , 48 , 51–53 , 62 …”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported MLA evaluations at stage II (retrospective), 32 , 33 , 36 , 38–40 , 45 , 48 , 49 , 55–57 2 at stage III (silent trial), 33 , 41 4 at stage IV (pilot trial), 50 , 58–60 3 at stage V (large trial/roll-out), 33 , 46 , 61 and 11 reported post-deployment evaluations. 35 , 37 , 42–44 , 47 , 48 , 51–53 , 62 …”
Section: Resultsmentioning
confidence: 99%
“…Essas tecnologias baseadas em IA têm auxiliado na reestruturação e contribuído para melhorias significativas em todas as esferas da prestação do cuidado desde a prevenção, diagnóstico precoce, predição de prognóstico, otimização das intervenções e tratamento de suporte [91]. No Brasil, entre outras iniciativas já aplicadas na rotina dos cuidados de saúde, dispositivos baseados em IA utilizados à beira leito para monitoramento de sinais vitais e biomarcadores têm se mostrado como ferramentas promissora para manejo e detecção precoce de condições complexas e graves como a sepse [92,93].…”
Section: Serviços Inteligentes Baseados Em Aprendizado De Máquinaunclassified